PENGARUH KONSELING GIZI PRAKONSEPSI DENGAN MEDIA VIDEO TERHADAP PENGETAHUAN DAN SIKAP CALON PENGANTIN PEREMPUAN DI PUSKESMAS SUKADAMAI LAMPUNG SELATAN - Tantri Wigati Putri; Megayana Yessy Maretta; Deny Eka Widyastuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
The nutritional status of women of childbearing age (WCA) or prospective brides during the preconception period, which lasts three to six months, determines the condition of the baby at birth. The nutritional and health status of prospective mothers during the preconception period, pregnancy, and breastfeeding is a critical phase. The prevalence of chronic energy deficiency (CED) in Lampung Province is 13.6%, while in South Lampung, it is 9.56%. Nutrition education promotes increased knowledge and behavioral changes. Counseling using video media is an effective health education method, as videos can provide more concrete information, be evenly distributed, repeated, or paused as needed, making them highly suitable for explaining processes. This study aims to determine the effect of preconception nutrition counseling using video media on the knowledge and attitudes of prospective brides at Sukadamai Public Health Center, South Lampung. This quantitative study uses a quasi-experimental design with a nonequivalent control group. The study population includes all prospective brides at Sukadamai Public Health Center, with an average of 50 individuals per month (January – June 2024). The sampling technique used is total sampling, with 25 participants in the intervention group and 25 in the control group. The study was conducted at Sukadamai Public Health Center. The intervention group received counseling using video media, while the control group received counseling using leaflet media. Data collection was conducted using observation sheets, and the analysis was performed using the Wilcoxon test, independent t-test, Mann-Whitney test, and paired t-test. The average knowledge score of prospective brides in the experimental group increased from 50.80 before the intervention to 79.80 after receiving counseling with video media, while in the control group, it increased from 52.40 to 62.40 after receiving counseling with leaflet media. Similarly, the average attitude score of prospective brides in the experimental group increased from 44.88 to 76.40, whereas in the control group, it increased from 46.88 to 66.00. The results showed a significant difference in the knowledge and attitudes of prospective brides before and after the intervention in both the video counseling group and the leaflet counseling group, with a p-value of 0.000. It is recommended to develop more interactive and engaging video media and involve prospective grooms in preconception nutrition counseling to enhance educational effectiveness and support optimal pregnancy preparation.